2014
DOI: 10.1055/s-0034-1368353
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Terpenes from Flowers of Inula japonica

Abstract: Five new terpenes (1-5) and ten known compounds (6-15) were isolated from Inula japonica, and their structures were identified by spectroscopic analysis. Compounds 3 and 14 showed positive inhibitory effects on nitric oxide production. Furthermore, compound 14 suppressed both leukotriene C4 synthesis and degranulation in c-kit ligand-induced bone marrow-derived mast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Two new (1, 2) and twelve known compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were isolated by various chromatographic separations from the EtOAc extract of the flowers of I. japonica (Fig. 1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two new (1, 2) and twelve known compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were isolated by various chromatographic separations from the EtOAc extract of the flowers of I. japonica (Fig. 1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Structures of 3-14 were identified by comparison of 1 H-and C 13 -NMR, FAB-MS spectral data and optical rotation values with those previously reported to be budlein B (3), 23) 6β-hydroxytomentosin (4), 24) 6-deacetoxybritanin (5), 25) 4-epipulchellin (6), 26) britanin (7), 27) tomentosin (8), 28) (+)-dihydroquercetin (9), 29) (−)-syringaresinol (10), 30) quercetagetin 3,4′-dimethy ether (11), 31) luteolin (12), 32) britanin G (13) 33) and inuchinenolide C (14) 34) (see the Supplementary materials). These compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were tested for inhibitory activities of DNA topoisomerases I and II (Fig. 5, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such compounds exhibit a variety of pharmacological activities, including cytotoxic and antitumor activities, and consequently, plants containing these compounds are promising ingredients for novel anticancer candidate drugs of natural origin [30]. Inula britannica is an erect, sunflower-like, herbaceous biennial or perennial plant in the Asteraceae family and its flowers are used in traditional Chinese medicine for the treatment of various diseases, such as digestive disorders, bronchitis, and inflammation [31]. This plant has been shown to contain high levels of sesquiterpenes, and some of these sesquiterpenes, especially sesquiterpene lactones, have been reported to exhibit potent cytotoxic and apoptotic activities [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we demonstrated that flower extract of I. japonica showed anti-inflammatory and anti-asthmatic activities in vivo and in vitro [4,20,26]. We also isolated several compounds from I. japonica and determined their anti-inflammatory activities [33]. Britanin, another compound isolated from the flowers of I. japonica, inhibited the production of NO and prostaglandin E2 (PGE2) in LPS-stimulated RAW264.7 cells [25].…”
Section: Introductionmentioning
confidence: 99%